Study on home energy management system with battery storage for peak load shaving. (2021) - Teki, Vamsee Krishna; Maharana, Manoj Kumar; Panigrahi, Chinmoy Kumar
Abstract: Demand for electricity is increasing day-by-day for the development of new technological innovations. Because of an increase in demand, there are specific issues like demand and supply mismatch. To reduce the peak load demand, increasing of a generation with the help of fossil fuels may lead to the release of pollutant gases like NOx and SO2 into the atmosphere. To reduce demand, renewable sources are playing a crucial part in the present power system scenario. These renewable energy sources with a battery storage system, used with particular control and energy management, are useful for peak load shaving. In this paper, we have modelled a Solar Photovoltaic system with battery storage for the residential load of 5KW as a complimentary supply and grid power as a primary supply, composed with power conditioning controller to reduce the load demand.